The Dialectics of Mercy and Justice:: Prophetic Ethics and the Limits of Compassion Toward Adversaries - Moh. Nadhif; Asrofik; Salman Khalid bin Othman (Excelencia: Journal of Islamic Education & Management, 2026)
This study examines the dialectical relationship between mercy (rahmah) and justice (‘adl) in Islamic teachings through a critical analysis of Prophetic ethics, with particular focus on the limits of compassion toward adversaries. While Islam is widely recognized as a religion of mercy, existing scholarship often treats compassion as an unconditional moral ideal, without sufficiently addressing its ethical boundaries in relation to justice. This study aims to explore how the Prophetic model negotiates the tension between mercy and justice, and how this dialectic can be rearticulated within contemporary Islamic thought. Employing a qualitative and interpretative approach, the research analyzes Qur’anic verses, Prophetic traditions, and modern Islamic ethical discourse. The findings reveal that Prophetic ethics embody a dynamic equilibrium in which mercy is upheld as a universal principle, yet constrained by normative limits to prevent injustice. Furthermore, excessive emotional leniency (ra’fah) is identified as a critical ethical risk that may undermine justice if left unchecked. This study contributes to Islamic ethical theory by proposing a dialectical framework that defines the limits of compassion within a justice-oriented moral system, offering significant implications for conflict ethics, interreligious engagement, and contemporary moral philosophy